Analysis of PSI and PDIP Political Marketing Strategies in the 2024 Election - Muhammad Ardi Firdiansyah; Abdul Fatah Alaudin Benihingan; Muhammad Firdaus (Internasional Journal of Politics and Public Policy, 2024)
This research aims to analyze the political marketing strategies of the Indonesian Solidarity Party (PSI) and the Indonesian Democratic Party of Struggle (PDIP) in the 2024 Election. A qualitative approach was used using the literature study method, collecting data from journals, news and relevant literature. This research explores the positioning and differentiation of the two parties based on political marketing theory. PSI, as a new party, is trying to emphasize its branding as a party of young people through a campaign based on progressive and innovative ideology, while PDIP maintains its position as the dominant party that carries the spirit of struggle of the small people with a more mature approach. The research results show that PSI focuses on young voter segmentation strategies, while PDIP takes advantage of its long period to continue to dominate the national political stage. This research contributes to understanding the dynamics of political marketing strategies in Indonesia, especially in the 2024 elections.